1992
DOI: 10.1002/jso.2930500114
|View full text |Cite
|
Sign up to set email alerts
|

Arm function after axillary dissection for breast cancer: A pilot study to provide parameter estimates

Abstract: Sixty-three women participated in a study in Calgary, Alberta to assess the rate of arm recovery and factors affecting it up to one year after axillary node dissection for breast cancer. Outcomes included objective measures of swelling, mobility, and strength, and subjective assessments of pain (at rest and with movement) and stiffness. Approximately 42% of women had residual impairment of at least one type one year after surgery, the most common problems being pain (16%) and reduced grip strength (16%). Excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0
11

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(82 citation statements)
references
References 8 publications
5
66
0
11
Order By: Relevance
“…Interestingly, Hladiuk et al (15) reported that the only statistically significant predictors for pain at 12 months after surgery were a greater number of postoperative analgesic injections and pain at one month after surgery. In a recent study Keramopoulus et al (16) showed that upper limb pain occurred more frequently in patients who were over 60 years of age, who underwent modified radical mastectomy and who had 30-40 nodes dissected.…”
mentioning
confidence: 99%
“…Interestingly, Hladiuk et al (15) reported that the only statistically significant predictors for pain at 12 months after surgery were a greater number of postoperative analgesic injections and pain at one month after surgery. In a recent study Keramopoulus et al (16) showed that upper limb pain occurred more frequently in patients who were over 60 years of age, who underwent modified radical mastectomy and who had 30-40 nodes dissected.…”
mentioning
confidence: 99%
“…Axillary lymph node dissection, however, is directly responsible for most of the side-effects related to breast surgery (Hladiuk et al, 1992;Robinson et al, 1992) and it requires general anaesthesia, thus adding treatment morbidity and costs. In addition, with the growing implementation of breast cancer screening programmes, and with the more favourable stage spectrum of newly detected breast cancers, systematic ALND would clearly be an overtreatment for most patients.…”
mentioning
confidence: 99%
“…0=ağrısız ve 10=en şiddetli ağrı olduğu anlatılıp, hastanın ağrısı-na karşılık gelen değeri skala üzerinde işaretlemesi istendi (21). VAS ≥1 ağrı olarak tanımlandı (22).…”
Section: Omuz Ağrısıunclassified
“…Meme kanseri, hastalığın kendi doğasından, radikal cerrahi girişimler ve radyoterapi uygulamalarından kaynaklanan çeşitli fonksiyon kayıplarına yol açabilmek-tedir. Bunlar arasında omuz disfonksiyonu (ağrısı ve eklem hareket kısıtlılığı), üst ekstremite kas gücü kaybı ve lenfödem gibi lokomotor sistem bozuklukları yanı sıra psikolojik ile kozmetik sorunlar sayılabilir ve sonuç olarak bu sorunlar kişilerin yaşam kalitesini (YK) etkilemektedir (7)(8)(9)(10)(11).…”
Section: Introductionunclassified